A new species of pseudopaludicola (Anura, leptodactylidae, leiuperinae) from the state of Minas Gerais, Brazil - de Andrade, Felipe Silva; Haga, Isabelle Aquemi; Lyra, Mariana Lúcio [UNESP]; de Carvalho, Thiago Ribeiro [UNESP]; Haddad, Célio Fernando Baptista [UNESP]; Giaretta, Ariovaldo Antonio; Toledo, Luís Felipe (Museum National D'Histoire Naturelle, 2018)
The genus of Neotropical frogs Pseudopaludicola Miranda-Ribeiro, 1926 includes 23 species, which occur throughout South America. Herein we describe a new species of Pseudopaludicola from the central region of the state of Minas Gerais (southeastern Brazil). This new species is distinguished by the adult morphology, the advertisement call, and molecular data. It is diagnosed mainly by its small size, terminal phalanges knobbed (lack of any expansion of the digital tips), proportionally short hind limbs, and its advertisement call composed of series of two-pulsed notes, emitted at a high repetition rate. In addition, we report the occurrence of the new species in the southern foothills of the Serra do Cipó National Park, at elevations lower than 800 m above sea level (a.s.l). The sister species of this new taxon is P. mineira Lobo, 1994, which occurs in rupestrian grasslands above 1200 m a.s.l. at the Serra do Cipó National Park and in Serra do Cabral, both in the state of Minas Gerais, Brazil. We also redescribe the advertisement call of P. mineira based on recordings from topotypical males and compare it to calls of related species.
Keywords: Advertisement call; Integrative taxonomy; Nov; Pseudopaludicola matuta sp; Pseudopaludicola mineira; Serra do Cipó National Park